9A9 Composite Loube I(re) I Magic Squares Infinite Abelian Group as a Miscellany Case of the 3A3 Loube I(re) I Magic Squares Infinite Abelian Group (Global Journal of Science Frontier Research, 2015)
In this paper, mystic miscellaneous algebraic properties of the set of 9 × 9 Composite (Nested) Loubere ́́ Magic Squares are vividly visualized. And, verbatim virtuoso of algebraic properties of the 3 × 3 Loubere ́́ Magic Squares viz: Eigen group, Magic Sum group and Centre Pieces group viewed the algebraic properties of its 9 × 9 Composite. It is also showcased that both the 2 sets equipped with the matrix binary operation of addition form infinite additive abelian groups.
Keywords: composite−; louberé −; abelian group; eigen group; magic sums; centre pieces